2015
DOI: 10.1016/j.bmcl.2014.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of 5-(2,6-dichlorophenyl)-3-hydroxy-2-mercaptocyclohex-2-enones as potent inhibitors of human lactate dehydrogenase

Abstract: Optimization of 5-(2,6-dichlorophenyl)-3-hydroxy-2-mercaptocyclohex-2-enone using structure-based design strategies resulted in inhibitors with considerable improvement in biochemical potency against human lactate dehydrogenase A (LDHA). These potent inhibitors were typically selective for LDHA over LDHB isoform (4–10 fold) and other structurally related malate dehydrogenases, MDH1 and MDH2 (>500 fold). An X-ray crystal structure of enzymatically most potent molecule bound to LDHA revealed two additional inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…The inhibitory activities of the newly prepared compounds 7a-7h were measured by standard enzyme experiments [9] on the two purified human enzyme isoforms LDHA and LDHB. The enzymes were dissolved in a 0.1 M phosphate buffer solution at pH 7 in the presence of the NADH, pyruvate, and the compounds 7a-7h.…”
Section: Enzyme Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibitory activities of the newly prepared compounds 7a-7h were measured by standard enzyme experiments [9] on the two purified human enzyme isoforms LDHA and LDHB. The enzymes were dissolved in a 0.1 M phosphate buffer solution at pH 7 in the presence of the NADH, pyruvate, and the compounds 7a-7h.…”
Section: Enzyme Inhibitionmentioning
confidence: 99%
“…Dichloroacetate (DCA), a promising pyruvate dehydrogenase kinases (PDK) inhibitor, whose function was to up-regulate the oxidative phosphorylation of pyruvate, thus weakening the Warburg effect in tumor cells [8]. The conversion of glucose to lactate under anaerobic conditions involves the enzyme lactate dehydrogenase A (LDHA, known as LDH-5) [9][10][11][12][13], while another isoform of lactate dehydrogenase (LDHB, known as LDH-1) preferentially catalyzes the reverse reaction in which lactate is converted to pyruvate [14]. It has been known for several decades that LDHA is Electronic supplementary material The online version of this article (doi:10.1007/s00706-015-1513-9) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, novel inhibitors were developed through either a fragment based approach by AstraZeneca [21] and Ariad Pharmaceuticals [22], or screening by Genentech [23] and GSK [24]. Even though some of the reported compounds showed inhibitory activity at low micromolar and nanomolar range, the authors reported limited cellular activity or not suitable pharmacokinetic properties.…”
Section: Introductionmentioning
confidence: 96%
“…Silencing by sh RNA or chemical inhibition of h LDH5 induces a decrease of cell proliferation and migration [ 2 , 3 , 4 , 5 , 6 ]. In the last decade, h LDH5 has gained a considerable attention as an attractive and potentially safe therapeutic target, and many inhibitors either synthetic [ 7 , 8 , 9 ] or isolated from natural sources [ 10 , 11 ] have been reported in literature. Nevertheless, inhibition of this enzyme remains a challenging goal, since the active site of h LDH5 comprises both a substrate binding pocket, which usually hosts the small polar structure of the substrate pyruvate, and a cofactor binding site, where NADH, which is more extended than the substrate and is composed of lipophilic as well as polar portions, is located.…”
Section: Introductionmentioning
confidence: 99%